Molecular and Cellular Mechanisms for Proteinuria in Minimal Change Disease - Bertelli, Roberta; Bonanni, Alice; Caridi, Gianluca; Canepa, Alberto; Ghiggeri, G. M. (Frontiers in Medicine, 2018)
Minimal Change Disease (MCD) is a clinical condition characterized by acute nephrotic syndrome, no evident renal lesions at histology and good response to steroids. However, frequent recurrence of the disease requires additional therapies associated with steroids. Such multi-drug dependence and frequent relapses may cause disease evolution to focal and segmental glomerulosclerosis (FSGS) over time. The differences between the two conditions are not well defined, since molecular mechanisms may be shared by the two diseases. In some cases, genetic analysis can make it possible to distinguish MCD from FSGS; however, there are cases of overlap. Several hypotheses on mechanisms underlying MCD and potential molecular triggers have been proposed. Most studies were conducted on animal models of proteinuria that partially mimic MCD and may be useful to study glomerulosclerosis evolution; however, they do not demonstrate a clear-cut separation between MCD and FSGS. Puromycin Aminonucleoside and Adriamycin nephrosis are models of glomerular oxidative damage, characterized by loss of glomerular basement membrane polyanions resembling MCD at the onset and, at more advanced stages, by glomerulosclerosis resembling FSGS. Also Buffalo/Mna rats present initial lesions of MCD, subsequently evolving to FSGS; this mechanism of renal damage is clearer since this rat strain inherits the unique characteristic of overexpressing Th2 cytokines. In Lipopolysaccharide nephropathy, an immunological condition of renal toxicity linked to B7-1(CD80), mice develop transient proteinuria that lasts a few days. Overall, animal models are useful and necessary considering that they reproduce the evolution from MCD to FSGS that is, in part, due to persistence of proteinuria. The role of T/Treg/Bcells on human MCD has been discussed. Many cytokines, immunomodulatory mechanisms, and several molecules have been defined as a specific cause of proteinuria. However, the hypothesis of a single cell subset or molecule as cause of MCD is not supported by research and an interactive process seems more logical. The implication or interactive role of oxidants, Th2 cytokines, Th17, Tregs, B7-1(CD80), CD40/CD40L, c-Mip, TNF, uPA/suPAR, Angiopoietin-like 4 still awaits a definitive confirmation. Whole genome sequencing studies could help to define specific genetic features that justify a definition of MCD as a “clinical-pathology-genetic entity”.